(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Construction is a vital part of every developing country in this era. Every country has specific building design codes which provide the standards to engineers for the design of various structural components like beam, column and slab. RC building design of every country is based on their geographical location. In today world of globalization, an engineer must be efficient to understand and handle codes of various countries. Considering this the main focus of this research work is to bring out differences and similarities between different RC design codes and to use it to develop a common platform. In this research RC design code of NEPAL, INDIA are considered. The main focus is the relative gains and shortcomings of various buildings design codes under certain criteria like loading analysis, design analysis, ease of use and economical point of view. Several parameters for different cross-section and different building material on basis of strength are considered. Comparison work has worked out on the basis of loading comparison like live load, dead load, wind load and different parameters for various elements of the building such as beam, column and slab. Load factor and load combination are also compared. This comparison investigates the design capacities for various building design codes.In present study RCC building models having G+8 stories with regular plan is considered for analysis. The analysis of model is done using equivalent static method in ETABS software.